Employment-related musculoskeletal complications experienced by the physical therapists in Bangladesh: a comprehensive cross-sectional case study - Amran Hossain; Tasnuva Shamarukh Proma; Rashaduzzaman Raju; Sharmin Ahmed; Ariful Islam (Bulletin of Faculty of Physical Therapy, 2022)
Abstract Background Dentists, nurses, and physical therapists have all been associated with an increased risk of work-related diseases. The findings of studies in these different occupations might aid in the development of preventative measures. In Bangladesh, however, no comparable evidence has been recorded among physical therapists. The study’s goal was to find out the prevalence of work-related physical problems at different anatomical locations, as well as the link between these disorders and treatment strategies across Bangladeshi physical therapists. Methods A physical and online survey of Bangladeshi physical therapists was done. A total of 300 questionnaires were given out, with work-related discomfort or pain detected in nine locations of the body: (1) neck, (2) shoulder, (3) elbow, (4) wrists, (5) upper back, (6) lumbar, (7) thighs, (8) knee, and (9) ankle. Results 85.5% of Bangladeshi physical therapists suffer musculoskeletal problems, according to the results of this research. The neck (25.7%), lower back (15.2%), elbow (12.3%), ankle (8.6%), and shoulder (8.6%) were the most often affected locations (7.1%). Upper back (3.0%) and hips (2.2%) ailments had the lowest prevalence. Conclusion Work-related musculoskeletal illnesses were common among the Bangladeshi physical therapists, especially in their neck, lower back, elbow, and ankle regions.